Probing the Impact of Porosity on Swelling Kinetics of Hydrophilic Matrices - Muhammad S Asim; Muhammad U Ghori; Barbara R Conway (University of Huddersfield Press, 2017)
The aim of the present investigation was to understand the swelling behaviour of HPMC and PEO-based matrices and to evaluate the impact of porosity on the swelling kinetics. It was noticed that the HPMC has higher swelling rates but both undergo diffusion oriented swelling mechanism. It could also the concluded that the porosity has a marked influence in the development of gel layer on the surface of these matrices.